HSV-1 Encephalitis in an Elderly Man Receiving Ibrutinib for Waldenstrom’s Macroglobulinemia - Mark R. Wallace (Case Reports in Infectious Diseases)
Ibrutinib is a major new addition to the therapeutic armamentarium for chronic lymphocytic leukemia, mantle cell lymphoma, Waldenstrom’s macroglobulinemia, and chronic graft versus host disease. Though ibrutinib has proven to be a revolutionary new small molecule agent, and has relatively minimal toxicity as compared to traditional chemotherapy, infections have emerged as a major complication of therapy. While fungal infections have been the most problematic (including CNS aspergillosis), zoster, hepatitis B reactivation, and chronic hepatitis E have been reported in association with ibrutinib therapy. This report describes a case of herpes encephalitis in an 86-year-old Waldenstrom’s patient receiving ibrutinib and speculates as to whether this late life encephalitis may have been related to ibrutinib.